The Genomic Basis of Intrinsic and Acquired Antibiotic Resistance in the Genus Serratia - Sandner-Miranda, Luisa; Vinuesa, Pablo; Cravioto, Alejandro; Morales-Espinosa, Rosario (Frontiers in Microbiology, 2018)
Serratia marcescens, a member of the Enterobacteriaceae family, was long thought to be a non-pathogenic bacterium prevalent in environmental habitats. Together with other members of this genus, it has emerged in recent years as an opportunistic nosocomial pathogen causing various types of infections. One important feature of pathogens belonging to this genus is their intrinsic and acquired resistance to a variety of antibiotic families, including ß-lactam, aminoglycosides, quinolones and polypeptide antibiotics. The aim of this study was to elucidate which genes participate in the intrinsic and acquired antibiotic resistance of this genus in order to determine the Serratia genus resistome. We performed phylogenomic and comparative genomic analyses using 32 Serratia spp. genomes deposited in the NCBI GenBank from strains isolated from different ecological niches and different lifestyles. S. marcescens strain SmUNAM836, which was previously isolated from a Mexican adult with obstructive pulmonary disease, was included in this study. The results show that most of the antibiotic resistance genes (ARGs) were found on the chromosome, and to a lesser degree, on plasmids and transposons acquired through horizontal gene transfer. Four strains contained the gyrA point mutation in codon Ser83 that confers quinolone resistance. Pathogenic and environmental isolates presented a high number of ARGs, especially genes associated with efflux systems. Pathogenic strains, specifically nosocomial strains, presented more acquired resistance genes than environmental isolates. We may conclude that the environment provides a natural reservoir for antibiotic resistance, which has been underestimated in the medical field.